Sexual Harassment in the University Context: Projective Diagnostic Study of Gender Situation at the Universidad de Santiago de Chile [Acoso Sexual en el Contexto Universitario: Estudio Diagnóstico Proyectivo de la Situación de Género en la Universidad de Santiago de Chile] - Lizama-Lefno, A (Pontificia Universidad Catolica de Chile, 2019)
Gender violence is a problem within university environments, which affects mostly to women and manifests itself in different ways. Sexual harassment is one of them, and continues to be a widely naturalized reality and as a consequence, barely visible. This article presents the results of the Projective Diagnosis Study of Gender Situation at the University of Santiago related to this phenomenon. It reveals a current and inescapable problem expressed in a high prevalence, a clear naturalization of verbal and gestural harassment, and a high percentage of unreported events associated with motives sustained in labor relations of fear and distrust, as well as lack of protection and institutional neglect related to the problem of sexual violence. This publication also aims to lay the foundations for addressing sexual violence in university contexts through the performance of diagnostic studies as part of processes to promote equality and how to deal with one of the important problems of sexual violence which higher education institutions are currently facing. © 2019 PEL.